An innovative technology of fracturing hard strata from the ground for precontrol of rock burst in a coal mine. Issue 2 (24th November 2022) - Tai, Yang; Yu, Bin; Kuang, Tiejun; Shi, Bowen; Meng, Xiangbin; Fu, Maoquan
Abstract: Rock bursts are one of the most common dynamic disasters in coal mines and seriously affect safety production. At present, there are three common types of rock bursts: fault‐structure, fold‐structure, and thick/hard‐roof rock bursts. First, the paper proposed an innovative technology for mine ground fracturing to control those rock bursts. Then, for the new method, its fracturing devices, process, and monitoring technique for cracks were introduced. Next, we analyzed the detailed control procedures for those types of rock bursts and control principles of absorbing energy, blocking stress transmission, and reducing overall rock strength. To illustrate the control effect of ground fracturing for the rock bursts, we proposed a Voronoi block division method (VBDM) and multistrength criteria (MSC) consisting of Mohr–Coulomb Joint, Hoek–Brown Joint, and strain–stress equivalent method. Then, two numerical models using the VBDM and MSC were established. One is fault‐structure rock burst with ground fracturing and another is that without. From the numerical simulation, it was concluded that: (1) The ground fracturing will increase τ / σ n, a ratio of shear stress to the normal stress of the fault, from 0.25 to 0.50, especially within 100 m of a working face to a fault. This situation indicates that ground fracturing will induce fault slip in advance, thus releasing energy in advance. (2) Fractured zones with low stress were formed by ground fracturing, which can reduce both upward extrusion pressure and normal stress, thereby triggering the fault slippage in advance. The energy released from the fault can be absorbed by the fractured zone, thereby controlling the advanced stress of the working face, and lowering the danger of rock burst. Abstract : Rock bursts are one of the most common dynamic disasters in coal mines and seriously affect safety production. For three different types of rock bursts (fault‐structure, fold‐structure, and thick/hard‐roof rock bursts), this paper proposed a rock burst control method based on mine ground fracturing so as to eliminate the danger.